Solid-state compounds of 4-chlorobenzylidenepyruvate with lanthanides preparation and thermal studies - Fernandes, N. S. [UNESP]; Carvalho Filho, M. A S [UNESP]; Melios, C. B. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2000)
Solid-state compounds Ln-4Cl-BP, where Ln represents lighter trivalent lanthanides and 4Cl-BP is 4-chlorobenzylidenepyruvate, were prepared. Thermogravimetry, derivative thermogravimetry (TG and DTG), differential scanning calorimetry (DSC) and other methods of analysis were used to characterize and to study the thermal behaviour of these compounds.
Keywords: Differential scanning calorimetry; Lanthanum compounds; Pyrolysis; Stoichiometry; Thermal effects; Thermodynamic stability; Thermogravimetric analysis; X ray powder diffraction; Chlorobenzylidenepyruvate; Derivative thermogravimetry; Lighter trivalent lanthanides; Solid state compounds; Chlorine compounds